PENINGKATAN KUALITAS PEMBELAJARAN DENGAN MODEL PROBING PROMPTING DALAM MATA KULIAH KONSEP IPS - Suyanti Suyanti (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2020)
This research has the purpose of knowing the improvement of learning quality with Probing prompting model in the course of the IPS concept for students of the study Program faculty of Teacher Training and Education Sciences, PGRI University Madiun. This type of research is PTK research action participants. The research site in the study program of Education elementary school teacher at Universitas PGRI Madiun. The implementation time of this research in the semester odd 2019/2020 course basic concept IPS. This research carried out several phases in its research, such as: monitoring, results, evaluation and reflection. Data analysis techniques in the form of quantitative description. Results of the conclusion of this study show: 1). The model of learning with Probing Promting model can improve the quality of course study of the DasarIPS concept, can be seen from the level of student activity, and test results. 2). Students love this model of defense because it makes them always active in learning.Keywords: Learning, IPS, Prombing Prompting.